Legal Protection of Children's Immovable Property Under Guardianship Based on the Decision of the Judge of the Surakarta Religious Court Islamic Law Perspective - Muh. Riefqi Aryadi; Muthoifin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The aim to be achieved in this writing is to find out whether in practice the legal protection of immovable property belonging to minors is in accordance with the statutory regulations or is it still far from being appropriate. The ideal arrangement for guardianship of children in conflict with the law is as regulated in Article 33 of the Child Protection Law, by reconstructing and dividing the two phrases of guardianship, namely guardianship in the civil aspect which must be carried out through a court determination process, and the criminal aspect which is directly determined. an institution or body that is given the task and authority to carry out guardianship of children in conflict with the law without having to go through a court decision. So learn from the perspective of Islamic law towards guardians who manage immovable assets belonging to minor children. The research method used in this research is a qualitative research method, therefore the source of research data is obtained from observations, interviews and documentation that will be carried out at the Surakarta Religious Court as well as from various literature and other references related to the subject of discussion. The results of this research can be concluded that at every stage of the examination, whether in the inquiry, investigation, prosecution, or examination stage in court (Article 23 of the SPPA Law), Children in Conflict with the Law have the right to receive assistance from parents/Guardians and trusted people ( Article 3 letter j of the SPPA Law). And also guardianship cases at the Surakarta Religious Court from 2021 to 2023 will see more guardianship cases in 2021, around 52% compared to only 2% in 2023.